(untitled) (Journal of the College of Basic Education, 2023)
In this work Cobalt(III) Sulfasalazine complex was synthesized and characterized by micro elemental analysis (C.H.N), spectral methods (UV- visible) and (FT.IR ) , and other physical measurements (molar conductance in 10-3M solution of ethanol, magnetic susceptibility for solid complex and studied in solution using Job,s method to obtain metal to ligand (M:L) ratio for complex in ethanol , Furthermore , Microbial sensitivity test on five microorganisms were tested .